Conjugated polymers containing tetraphenylethylene in the backbones and side-chains for highly sensitive TNT detection. Issue 11 (2nd February 2018) - Dong, Wenyue; Fei, Teng; Scherf, Ullrich
Abstract : Polytriphenylamines with tetraphenylethylene (TPE) side groups and bis( tert -butyl)-TPE in the backbones exhibit the AIE effect and high sensitivity in PL-based TNT detection. Abstract : The novel polytriphenylamines derivatives PTPA1-TPE and PTPA2-TPE with TPE as side groups and bis( tert -butyl)-TPE in the backbones have been successfully synthesized via Yamamoto-type coupling under microwave heating. The incorporation of TPE units in the backbones and side-chains endows the polymers with a distinct AIE effect and high fluorescence quantum yields in the solid state. Meanwhile, nitroaromatic explosive detection based on dispersed, electron-rich PTPA1-TPE and PTPA2-TPE nanoaggregates in THF/water was carried out. Both of them show high sensitivity towards the TNT analyte, with a maximum Stern–Volmer quenching constant K sv of up to 8.3 × 10 4 M −1 . In addition, the paper strip test demonstrates the promising practical application of the polymers as solid state sensors towards PL-based nitroaromatic explosive detection.